Politik Identitas Marga Karo dalam Menentukan Pilihan Politik pada Pemilihan Kepala Desa : (Studi Kasus Desa Kem-Kem Kecamatan Tigabinanga) (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Identity politics refers to a political instrument employed by a group—such as an ethnic community, tribe, cultural group, religion, or othersfor specific purposes, either as a form of resistance or as a means to assert the group’s identity. This form of politics is influenced by various factors, including religion, culture, tradition, and community leaders. This study aims to analyze the practice of identity politics within the village head election process in Kem-Kem Village, Tigabinanga District. A qualitative approach with a descriptive research design was employed. The research was conducted in Kem-Kem Village, using data collection techniques such as observation, in-depth interviews, and documentation. The data comprised both primary and secondary sources. Data analysis was carried out through the processes of data reduction, data display, and conclusion drawing (verification). The study examines the influence of clan-based identity politics in the village head election in Kem-Kem Village. The findings reveal that most community members continue to vote based on shared clan affiliation, driven by emotional and customary ties. However, a gradual shift toward rational politics has begun to emerge, particularly among the younger generation, who evaluate candidates based on work programs and competencies. The election of a village head from a minority clan serves as evidence of this change. Although the shift is not yet widespread, Kem-Kem Village demonstrates significant potential toward achieving a more equitable and rational form of local democracy.